2021
DOI: 10.1155/2021/4968300
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effect of Dexmedetomidine Combined with Ropivacaine on Cognitive Dysfunction and Inflammatory Response in Patients Undergoing Craniocerebral Surgery

Abstract: Objective. To study the effects of dexmedetomidine in combination with ropivacaine in patients undergoing craniocerebral surgery and their efficiency on cognitive function and inflammatory response of patients. Methods. 100 patients undergoing craniocerebral surgery in our hospital from November 2018 to September 2020 were randomly selected and divided into a control group and an experimental group by drawing lots, with 50 cases in each group. Patients in the control group received routine anesthesia, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Most of the trials did not report on our outcomes. A total of 106 RCTs and one sub‐study of an included RCT provided data for quantitative synthesis 43–149 . Six of the included trials reported a total of 15 eligible comparisons 60,62,82,124,145,147 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the trials did not report on our outcomes. A total of 106 RCTs and one sub‐study of an included RCT provided data for quantitative synthesis 43–149 . Six of the included trials reported a total of 15 eligible comparisons 60,62,82,124,145,147 .…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, our results revealed that DEX pretreatment notably reduced LDH release and repressed cell apoptosis. DEX combined with ropivacaine potently alleviates postoperative pain and improves cognitive function in patients receiving craniocerebral surgery [ 30 ]. DEX combined with ropivacaine not only prolongs the sensory and motor block duration of sciatic nerve in rats but also mitigates ropivacaine-induced neurotoxicity by suppressing caspase-3-dependent apoptosis of sciatic nerve cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that ropivacaine can cause neurotoxicity during the perioperative period, especially at a high concentration and/or for prolonged use [6]. DEX, a kind of α2 adrenergic receptor agonist, has been commonly used as an adjuvant of ropivacaine and has shown neuroprotective properties in multiple experimental models [28][29][30]. To the best of our knowledge, our study is the first-of-its-kind to demonstrate that DEX pretreatment alleviated ropivacaine-induced neurotoxicity via the miR-10b-5p/BDNF axis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery-induced tissue trauma and ischemia-reperfusion damage can activate the immune system, and then an in ammatory cascade response can be triggered (1)(2)(3). Neuroin ammation, which has catastrophic effects after both craniocerebral surgery and neurological diseases, such as epilepsy and Alzheimer's disease, is caused by a variety of in ammatory cytokines and in ammatory pathways (4,5). However, it is not entirely clear how these in ammatory cytokines have an impact on the brain when the surgical site is not in the brain.…”
Section: Introductionmentioning
confidence: 99%